Impact of cardiovascular comorbidity on increased neutrophil-lymphocyte ratio in pseudoexfoliation syndrome. Issue 28 (15th July 2022) - Oh, Hea Young; Lee, Mee Yon; Lee, Young Chun; Shin, Hye-Young
Abstract : Background: The purpose of this study was to compare neutrophil-to-lymphocyte ratios (NLRs) of patients with pseudoexfoliation syndrome (PEX) according to the presence of cardiovascular disease (CVD) with those without CVD as controls. Methods: A total of 197 participants (97 patients with PEX and 100 participants without PEX regarded as the control group) were included in this retrospective study. The PEX group was divided into 2 subgroups, PEX with CVD (group 1) and PEX without CVD (group 2). NLRs were then compared to those of the control group. Results: The incidence of CVD was significantly ( P = .015) higher in the PEX group than in the control group. NLR was significantly higher in the group 1 and group 2 compared with that of the control group ( P = .048 and P = .002, respectively). In the PEX group, group 1 showed higher NLR than group 2 ( P = .023). Conclusion: Although the PEX group showed a higher incidence of CVD, the NLR was higher in the PEX group regardless of cardiovascular comorbidity than that in the control group.